2004
DOI: 10.1163/1568530043068010
|View full text |Cite
|
Sign up to set email alerts
|

A Language of Their Own: An Interactionist Approach to Human-Horse Communication

Abstract: This paper explores the process of human-horse communication using ethnographic data of in-depth interviews and participant observation. Guided by symbolic interactionism, the paper argues that humans and horses co-create a language system by way of the body to facilitate the creation of shared meaning.This research challenges the privileged status of verbal language and suggests that non-verbal communication and language systems of the body have their own unique complexities. This investigation of humanhorse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 19 publications
1
95
0
6
Order By: Relevance
“…This study has revealed how, at this level, the horse-rider relationship differs markedly to that seen at lower levels of competition and with leisure riders (Brandt, 2004).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This study has revealed how, at this level, the horse-rider relationship differs markedly to that seen at lower levels of competition and with leisure riders (Brandt, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…However, the demands of the elite sporting world do not make space for failure (Hughes and Coakley, 1991) -be it human or equine. As a result, riders may be discouraged from forming close bonds with their horses, in the ways common for leisure riders (Brandt, 2004), as the relationship will probably be transient.…”
mentioning
confidence: 99%
“…Current consensus in science suggests that from the behaviour of animals we can conclude that they are likely to have positive and negative emotions, but it is impossible for us to know with any certainty how the animals experience those emotions in relation to how we as humans experience them (Mills 2013). I agree with Mangelsdorf (2013), who is referring to Brandt (2004) that it would be useful to create a 'third language' as an emphatic dialogue based on body language including movement and emotions. The only question is how this dialogue might be held and who will be the leader of this dialogue, so that in this dialogue horses might not mutually be considered again as inferior to humans by acting only out of their instincts, and their tribe and constitution-based attitude.…”
Section: Contextualization (2): Dancing Horses and Reflecting Humansmentioning
confidence: 59%
“…During the last fifteen years, the interest in equestrian communication has been on the rise in several research traditions, not the least within the humanities and social sciences (see for instance, Brandt, 2004;Brown, 2007;Birke, 2007Birke, , 2008Birke, , 2009Birke, , 2010Argent, 2012;Maurstad, Davis & Cole, 2013;Birke & Hockenhull, 2015;Thompson & Nesci, 2016;Dashper, 2016). Many of these qualitatively oriented studies are oriented towards Human-Animal Studies (HAS), but equestrian communication has also been studied within a research area referred to as Equitation Science (ES).…”
Section: Research On Equestrian Communicationmentioning
confidence: 99%